Boy meets girl - Cabot, Meg. (New York : Avon Trade, 2004)
Kate Mackenzie thinks life can't get any worse, until her tyrannical boss makes her fire the most popular employee in the department, leading to a lawsuit for wrongful termination, and a close encounter with a Manhattan lawyer who embodies everything Kate detests.
Booklist.
Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Adult
Keywords: Actions and defenses -- Fiction; Employees -- Dismissal of -- Fiction; Newspaper publishing -- Fiction; Personnel departments -- Employees -- Fiction; Employees -- Dismissal -- Fiction; Epistolary fiction; Humorous fiction; Legal stories; Litigation -- Fiction; Love stories; Personnel management -- Employees -- Fiction; Publishers and publishing -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction; Epistolary fiction; Humorous fiction; Legal stories; Love stories